2002
DOI: 10.1103/physrevd.65.124022
|View full text |Cite
|
Sign up to set email alerts
|

Abelian Higgs hair for rotating and charged black holes

Abstract: We study the problem of vortex solutions in the background of rotating black holes in both asymptotically flat and asymptoticlly anti de Sitter spacetimes. We demonstrate the Abelian Higgs field equations in the background of four dimensional Kerr, Kerr-AdS and Reissner-Nordstrom-AdS black holes have vortex line solutions. These solutions, which have axial symmetry, are generalization of the Nielsen-Olesen string. By numerically solving the field equations in each case, we find that these black holes can suppo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Now, by using the relaxation method [18] for the above finite difference equations (17) and (18) Refs. [4] and [7]- [14], increasing the winding number yields a greater vortex thickness. The black string horizon is located at r H = 0.6173 for Figs.…”
Section: Numerical Solutionsmentioning
confidence: 99%
“…Now, by using the relaxation method [18] for the above finite difference equations (17) and (18) Refs. [4] and [7]- [14], increasing the winding number yields a greater vortex thickness. The black string horizon is located at r H = 0.6173 for Figs.…”
Section: Numerical Solutionsmentioning
confidence: 99%
“…The first attempts to attack this problem were presented in Ref. [27], but the correct treatment of a Kerr black hole Abelian Higgs vortex was presented in [28].…”
Section: Introductionmentioning
confidence: 99%
“…It describes a thin cosmic string passing through a Schwarzschild black hole. It was revealed that it constituted the limit of a much more realistic situation when a black hole was pierced by a Nielsen-Olesen vortex [48][49][50][51][52][53][54][55]. In the extremal limit of the black hole under consideration a completely new phenomenon occurred.…”
Section: Discussionmentioning
confidence: 99%